KINETICS AND MECHANISM OF ELECTRON-TRANSFER REACTION : OXIDATION OF N-BUTANALDEHYDE BY N-CHLOROISONICOTINAMIDE IN AQUEOUS ACETIC ACID MEDIUM - Singh, Birendra; Vishwakarma, Umesh Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
N-chloroisonicotinamide uncatalyzed oxidation of butanaldehyde in aqueous acetic acid, and sulfuric acid medium was investigated at 313 K. Data indicate the reaction follows identical kinetics with first-order in [oxidant]. The reaction rate shows direct proportionality with respect to low [substrate], which tends to become zero-order at higher concentrations of the butanaldehyde, and inverse fractional-order in [H+] that follows kobs = a + b [H+]. The rate increased with decreasing dielectric constant of the medium. The variation of ionic strength, and the addition of reaction product (isonicotinamide) had no significant effect on reaction rate. The stoichiometric ratio was assigned 1:1 in H2O+Cl reacting species of oxidant mechanism with rupturing C-H bond of substrate to yield n-butyric acid product. The activation parameters associated with the rate-determining step have been computed. The proposed mechanism, and the derived rate law are consistent with the observed kinetic data.